FRW Viscous Cosmology for Varying \(G\), \(c\) and \(Λ\), with Inhomogeneous Equation of State - Ghogre, A. S.; Khadekar, G. S.; Raut, Deepti (Communications in Mathematics and Applications, 2023)
In this paper, the Freidmann equations described by inhomogeneous equation of state (EOS) of the form \(p= (γ-1)ρ c^{2}+Λ(t)\), for a bulk viscosity media, are considered. The time dependent parameter \(Λ\) is considered as a linear combination of the terms as \(Λ(t)=Λ_{0} + Λ_{1}\frac{\dot{R}}{R}\) and the bulk viscosity as \(ζ=ζ_{0}H^{-1} ρ\), where \(R\) is a scale factor and \(Λ_{0}\), \(Λ_{1}\) and \(ζ_{0}\), are all constants. The resultant equation to the scale factor is solved to get the exact solution by choosing some special parameters, in the framework of variable speed of light (VSL) theory.